Epidemiology, Risk Factors and Ways of Prevention Of Ischemic Heart Disease in the Population Of Fergana Valley Medical Workers (Eurasian Medical Research Periodical, 2023)
Studies have shown that even people between the ages of seventy and eighty who make changes in their diet and lifestyle show a significant reduction in the risk of developing diseases such as coronary heart disease. Some people live much longer than average, thanks in part to their DNA. study published in the European Heart Journal shows that this genetic code could be reproduced even for those who do not have it. The way is now open for an innovative model of therapy that can prevent and combat cardiovascular disease by truly rejuvenating the blood vessels.